Mobile health applications during epidemic management in India: a review - Ghosh, Rajgourab; Kumar, Sanjeev (EAI Endorsed Transactions on Smart Cities, 2020)
INTRODUCTION: Smart cities endeavour to provide a good quality of life to its inhabitants. The COVID-19 pandemic necessitates redrawing the framework of epidemic management in India. Information, Communication & Technology (ICT) solutions such as mobile health (mHealth) can complement this. OBJECTIVES: To review ICT and mHealth used for epidemic management in smart cities of India. METHODS: A systematic review was conducted to identify the use of ICT or mHealth applications for epidemic management in smart cities. A predefined search strategy and a predefined eligibility criterion to search for articles published in English on Medline were used. RESULTS: Our study showed ICT and mHealth use has increased during the recent COVID-19 pandemic in India and available solutions can be applied in smart city framework to improve epidemic management and achieve mHealth targets. CONCLUSION: We conclude that there have been many advances in the provisions of ICT and mHealth interventions in India in context to smart cities and scope for improvements abound.